2008
DOI: 10.1007/s10750-007-9269-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carbopol resin for carp pituitary administration improves the fertilization percentage of northern pike (Esox lucius Linnaeus) eggs in commercial hatcheries

Abstract: The efficiency of northern pike (Esox lucius Linnaeus) fry production via hormonal treatment of wintered broodstock is, in general, relatively low due to low egg fertilization percentage. It has been experimentally demonstrated that administration of acetone-dried carp pituitary extract in a slow-release vehicle of aqueous dispersion of Carbopol 971 P resin (CP) resulted in a higher mean fertilization percentage, possibly because the gradual hormone action could optimally control ovarian follicle maturation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…15: 575-581(2015) 578 injection. This is consistent with results of other studies that have used carp pituitary or other hormone gonadotropin-containing preparations (Billard and Marcel, 1980;Brzuska and Malczewski, 1989;Szabó, 2001Szabó, , 2003Szabó, , 2008. Szabó et al (2014) found similar ovulation efficacy for silver carp pituitary compared to carp pituitary in northern pike.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…15: 575-581(2015) 578 injection. This is consistent with results of other studies that have used carp pituitary or other hormone gonadotropin-containing preparations (Billard and Marcel, 1980;Brzuska and Malczewski, 1989;Szabó, 2001Szabó, , 2003Szabó, , 2008. Szabó et al (2014) found similar ovulation efficacy for silver carp pituitary compared to carp pituitary in northern pike.…”
Section: Discussionsupporting
confidence: 88%
“…One spontaneously ovulated female from group 3 had higher fertilization and hatching rates, however, these data were limited and not comparable to other groups. Generally, hatching and fertilization rates found in our study were higher than those reported by other authors (De Montalembert et al, 1978;Billard and Marcel, 1980;Horváth, 1983;Szabó, 2001;2003;2008).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In the two treatment groups females received an injection of a crude preparation of dried common carp or silver carp pituitary, respectively, at a dose of 3.5 mg kg -1 BW. Pituitaries were administered in a vehicle of a 2.5% aqueous dispersion of Carbopol resin (Szabó, 2008). Injections were applied intraperitoneally at a volume of 0.5 ml kg -1 BW.…”
Section: Methodsmentioning
confidence: 99%